An Ecological Study of Anterior Cruciate Ligament Reconstruction, Part 2: Functional Performance Tests Correlate With Return-to-Sport Outcomes. Issue 2 (15th February 2017) - McGrath, Timothy M.; Waddington, Gordon; Scarvell, Jennie M.; Ball, Nick; Creer, Rob; Woods, Kevin; Smith, Damian; Adams, Roger
Background: Additional high-quality prospective studies are needed to better define the objective criteria used in relation to return-to-sport decisions after anterior cruciate ligament (ACL) reconstruction in active populations. Purpose: To investigate prospectively the relationship between functional performance test results at 24 weeks postoperative and return-to-sport activity (Tegner activity score) at 12 and 24 months, respectively, after synthetic (ligament advanced reinforcement system [LARS]) and autograft (doubled semitendinosus/gracilis [2ST/2GR]) ACL reconstructions. Study Design: Case series; Level of evidence, 4. Methods: A total of 64 patients who underwent ACL reconstruction (32 LARS, 32 2ST/2GR autograft; mean age, 27.9 years; body mass index [BMI], 24.9 kg/m 2 ) were assessed preoperatively and at staged intervals postoperatively up to 24 weeks for isokinetic testing of quadriceps and hamstring average power per repetition at 60 deg/s and 180 deg/s, a battery of hop tests, peak vertical ground-reaction force (vGRF), and time to peak vGRF (in seconds) during a step- and jump-down task onto a force platform and peak speed (m/s) using a global positioning system (GPS unit) during a running task. A cohort of 32 healthy matched participants (mean age, 26.31 years; BMI, 25.7 kg/m 2 ) were also tested to act as reference. Pearson correlation was calculated to assess correlation of each performance measure at 24 weeks postoperative with activity outcomes (Tegner score) at 12 and 24 months. Results: The strongest correlation between physical performance tests and return-to-sport outcomes was observed with peak speed during running. Large correlations were also observed for hamstring isokinetic power and hop test for distance. Moderate correlations were observed for timed hop, peak vGRF during a jump-down task, and quadriceps isokinetic power. No statistical correlations were observed for time to peak vGRF during a step-down and jump-down task as well as peak vGRF during a step-down task. When the performance tests were pooled together, mean postoperative improvements of 24% were observed from preoperative to 24 weeks within the surgical cohort. For each performance test, preoperative level of function strongly correlated with performance levels on the same test at 24 weeks. Discussion: The results of this study indicate that clinicians might seek to prioritize these tests and the rehabilitation themes they imply when seeking to maximize postoperative ACL activity outcomes. The observed strength between pre- and postoperative performance tests and return-to-sport outcomes within this study highlights the potential value of preoperative conditioning before undergoing ACL reconstruction. Future research should examine absolute predictive criterion thresholds for functional performance-based tests and reinjury risk reduction after ACL reconstruction.